Top managers' characteristics as causal explanations for self-reported performance - Guedes, Maria João (2022)
We use a fuzzy-set qualitative comparative analysis to examine how four characteristics of top managers (narcissism, sense of control, tenure, and workload) explain their high or low self-reported performance. Our survey sample comprises 784 top managers (572 males and 212 females) from non-listed firms in all industries in Portugal. While the results show that none of the characteristics is either a necessary or sufficient condition, they do show that three different paths exist that are conducive to high self-reported performance. The results indicate that the self-images of the managers and the control they exert over others influence their judgements about their performance and the reality of the firm. This finding highlights the important effect that top managers' characteristics have on performance, and stakeholders should consider this effect when analyzing a firm.